Anaerobic oxidation of methane coupled to thiosulfate reduction in a biotrickling filter. (September 2017) - Cassarini, Chiara; Rene, Eldon R.; Bhattarai, Susma; Esposito, Giovanni; Lens, Piet N.L.
Graphical abstract: Highlights: A BTF was tested for anaerobic methane oxidation in the presence of thiosulfate. Thiosulfate disproportionation was observed in the BTF. The DSS population was enriched after long term (213 days) BTF operation. Thiosulfate reduced the reactor start-up time and increased the sulfate reduction rate. Abstract: Microorganisms from an anaerobic methane oxidizing sediment were enriched with methane gas as the substrate in a biotrickling filter (BTF) using thiosulfate as electron acceptor for 213 days. Thiosulfate disproportionation to sulfate and sulfide were the dominating sulfur conversion process in the BTF and the sulfide production rate was 0.5 mmol l −1  day −1 . A specific group of sulfate reducing bacteria (SRB), belonging to the Desulforsarcina/Desulfococcus group, was enriched in the BTF. The BTF biomass showed maximum sulfate reduction rate (0.38 mmol l −1  day −1 ) with methane as sole electron donor, measured in the absence of thiosulfate in the BTF. Therefore, a BTF fed with thiosulfate as electron acceptor can be used to enrich SRB of the DSS group and activate the inoculum for anaerobic oxidation of methane coupled to sulfate reduction.